Risk for acute kidney injury in primary health care - Rigonatto,Maria Célia Laranjeira (2018)
ABSTRACT Objective: To identify hypertensive and diabetic patients at risk for developing acute kidney injury in the primary health care setting. Method: Observational, longitudinal, prospective study. Sample of 56 diabetic and hypertensive individuals. A semi-structured questionnaire was adopted for data collection. For the description of results, were calculated dispersion measures and the Spearman test was used for statistical analysis. The result was considered significant when p <0.05. Results: Of the total sample, 23.2% of users evolved with renal impairment, of which 19.6% with risk for renal injury, and 3.6% with kidney injury itself. Age and body mass index were associated with worsening of renal function (p = 0.0001; p = 0.0003), respectively. Conclusion: A quarter of the health system users, hypertensive and diabetic, evolved with impaired renal function, more specifically to stages of risk for renal injury and kidney injury according to the RIFLE classification.